INTEGRATING CULTURAL HERITAGE AND MODERN URBAN PLANNING: TRANSFORMING KARANG BENGANG IN TEGALLALANG - Kardinal, Ni G. A. Diah Ambarwati; Putra, I Dewa Gede Agung Diasana; Adhika, I Made; Dwijendra, Ngakan Ketut Acwin (Department of Architecture, Institut Teknologi Sepuluh Nopember (ITS), 2024)
Karang bengang, a traditional green space in Tegallalang, Gianyar, represents a significant element of Bali's cultural heritage and environmental sustainability. This study explores integrating karang bengang's cultural and ecological values with modern urban planning strategies to create sustainable urban designs that honor traditional practices. A lot of karang bengang has been lost due to development, thereby changing the heritage site. The research employs a qualitative approach, including grounded theory and hermeneutic analysis, to understand the historical significance, current transformation, and future potential of karang bengang. Findings reveal that karang bengang serves not only as a green belt and community space but also as a vital component of Bali's cultural identity, offering ecological benefits and promoting social cohesion. However, rapid urbanization and tourism development threaten its existence and functionality. This study proposes a model that balances development needs with preserving traditional landscapes. This model emphasizes community engagement, digital mapping technologies, and policy recommendations that reinforce the importance of cultural landscapes in urban environments. The proposed framework aims to guide policymakers, urban planners, and local communities in preserving karang bengang while accommodating growth and modernization. Ultimately, this research contributes to the broader discourse on sustainable urban development, highlighting the need to respect and incorporate cultural heritage in the planning process to achieve resilient and culturally enriched urban spaces.